The Effect of Packaging Materials on The Quality of Children's Jelly Candies with Artificial and Natural Color - Sana, S.H. Aly; Manal, A. El-Gendy (Food Technology Research Journal, 2023)
Natural red dyes extracted from red beetroots were identified (betalain) and determined as its usage in colored children’s candy because it has a safe effect on health, compared with artificial pigments (Carmosine). The jelly candy was colored using different concentrations (10, 15 and 30 %) of natural color, different packaging material was used (Metallized polypropylene MTPP, a box of polyester PET, high-density polyethylene HDPE and a two-sided package of Metallized polypropylene and transparent polypropylene MTPP+ TPP) and studied, the effect of packaging materials on the stability of pigment and the retention of the good color degree of degradation during storage at room temperature and the refrigerator was analyzed, the results indicated that the best extraction method of the natural pigment using 3% citric acid. Also, the best packaging material used for keeping the candy from deterioration was MTPP followed by PET, MTPP + TPP, while HDPE packages showed a clear deterioration of the natural and artificial pigments during storage. Adding 3% of the natural pigment to the candy was significantly better than 1, 2% and have higher sensory evaluation. The objective of the study is to extract of the natural betalain pigment from red beetroots and then use in coloring children's candy (jelly) compared with the artificial pigment (carmosine) study the effect of the packaging material on preserving the jelly from external influences, and study the stability of the betalain pigment during the storage period.